ICT feasibility study to empower ethnic craftswomen to transit to intangible heritage under digital technology disruption and SDG’s: "Leave no one behind" - Intraratat, Kamolrat; Lomchavakarn, Piyachat; Ng, Khar Thoe; Ng, Miew Luan; Intaratat, Duangkamol (Edelweiss Applied Science and Technology, 2024)
This study is qualitative research employing e-interviews, focus group discussions, and observations among the selected 15 key informants of craftswomen from three main ethnic tribes in Chiangmai province, North of Thailand named Karen, Akha, and Hmong together with the relevant stakeholders. Objectives are to study: 1) the socio-economic contexts of the three main ethnic craftswomen; 2) challenges and needs in terms of ICT and entrepreneurship skills; and 3) ICT and entrepreneurship skills needed to support the ethnic craftswomen to transit their intangible heritage. Findings found 1) similar demographic and socio-economic contexts among most of the three main ethnic craftswomen groups in their marginalized with least of formal education, less opportunities than male, but having a very important role to transit most of their tribal heritages both tangible and intangible heritages; 2) least of ICT knowledge and skills because of their misperceptions about ICT i.e. ICT is difficult, ICT is only designed for males and for the educated ones, and ICT is expensive. They need more ICT’s knowledge and skills to manage their own e- shops especially in e-banking, e-financial management, and e- orders respectively; 3) ICT needs found three main issues respectively : (1) ICT for documenting all crafts heritages; (2) ICT to transmit all the heritages through the new generations; and (3) more functional ICT for their better life and better entrepreneurship i.e. e-marketing, e-PR aims to be more visible and more functional in a better living, inclusion, and heritages’ pride.